Agroecological assessment of herbicides application on soybean crops in the central zone of Krasnodar Territory, Russia - A. P. Savva; T. N. Telezhenko; V. A. Suvorova (Юг России: экология, развитие, 2023)
Aim. Agroecological assessment of herbicides application on crops of soybean variety Arleta in the central zone of Krasnodar Territory.Materials and Methods. The experiments were carried out on the experimental field of the Federal Research Centre of Biological Plant Protection in 2022 according to the methodological recommendations for testing herbicides in agriculture. Herbicides from different chemical classes were used in the experiment. Efficiency was assessed by the difference in weed and soybean grain yield in comparison with the control. The comparative ecotoxicological load of preparations was carried out according to the ecological load and the coefficient of selectivity of action for the soil.Results. Weed species in the experiment were highly effectively suppressed by the herbicides Pulsar, BP, Pivot, VK and a mixture of Bazagran, BP + Zellek Super, and KE (88–98 %). When using Dual Gold, EC, Frontier Optima, EC and Proponit, and EC before the soybean shoots, the biological efficacy was lower. The preparations Pulsar, BP and Pivot, and VK, in comparison with other herbicides, had a lower level of environmental load and a high coefficient of selective action and meet modern safety requirements for the natural environment.Conclusions. In order to protect the environment when choosing herbicides for application on soybean crops in the central zone of Krasnodar Territory, they should be comprehensively selected taking into account the ecotoxicological load of the preparations.